PENINGKATAN HASIL BELAJAR SISWA PADA PEMBE LAJARAN IPS DENGAN MENGGUNAKAN MODEL COPERA TIVE LEARNING TIPE NUMBERED HEADS TOGET HER (NHT) DI KELAS IV SD NEGERI 18 AIR TAWAR SELATAN KOTA PADANG - wahyudi, diky; farida, farida; muhammadi, muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACT Diky Wahyudi, 2018. Improvement of Student Learning Outcomes in Running Learners Social Studies Learning Using the Num Bered Heads Together (NHT) Cooperative Learning Model in Class IV of SD Negeri 18 Air Tawar Selatan, Padang City. This research is motivated by the low learning outcomes of fourth grade students of SD Negeri 18 Air Tawar Selatan, Padang City in social studies learning, because teachers have not been optimal in making learning plans, lacking in developing thinking power, and students' creative power. Besides that, teachers lack training in this matter, and also with groups, which affects the low student learning outcomes. The purpose of the study was to describe an increase in student learning outcomes using the NHT model in class IV social studies learning at SD Negeri 18 Air Tawar Selatan, Padang City. This type of research is classroom action research using qualitative and quantitative approaches. The research procedure consists of planning, implementation, observation, and reflection. The research data consisted of processes and observations in social studies learning with the NHT model of Engineering completing data and tests. This research was conducted in Semester I Academic Year 2018/2019. The research subjects were teachers as observers, researchers as practitioners, and class IV students as many as 20 people consisting of 11 men and 9 women. The results of the study showed: (a) the RPP of the first cycle averaged 76.78% (B), the second cycle 96.42% (A), (b) the implementation on the teacher aspect of the first cycle an average of 72.11% (B) , cycle II 86.53% (A), (c) implementation on aspects of student cycle I average 62.49% (C), and cycle II 86.53% (A), (d) student learning outcomes cycle I an average of 62.49, and the second cycle 86.53. The results of the study using the NHT model can improve student learning outcomes in Social Studies learning in Grade IV SD Negeri 18 Air Tawar Selatan, Padang City.